Optimizing of Competitive Adsorption Methylene Blue and Methyl Orange using Natural Zeolite from Ende-Flores - Yulius Dala Ngapa; Jumilah Gago (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
Waste from the textile industry is considered a potential source of environmental pollution, especially water, because it contains dangerous dyes. In this research, natural zeolite is an effective and efficient alternative to overcome pollution caused by methylene blue and methyl orange dyes. Activation of natural zeolite was carried out with 3 M HCl solution and was characterized using X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM). Simultaneously, the methylene blue and methyl orange adsorption processes were studied in variations in the weight of the adsorbent, contact time, and pH. The concentration of dyes left in the solution was observed with UV-Vis Spectrophotometer. The results showed that the adsorption capacity of natural zeolite in absorbing methylene blue was 21.189 mg / g and methyl orange was 18.208 mg / g. The optimum conditions of dyes adsorption are achieved with successive adsorbent weights 0.3 g and 0,4 g, following contact times 60 minutes and 90 minutes, and successive pH 6 and 2. The adsorbent weight factor, contact time, and pH affect the adsorption of dyes by natural zeolite from  Ende.